In Vivo Expression and Immunoadjuvancy of a Mutant of Heat-Labile Enterotoxin of Escherichia coli in Vaccine and Vector Strains of Vibrio cholerae - Ryan, Edward T. (American Society for Microbiology, 1999)
Vibrio cholerae secretes cholera toxin (CT) and the closely related heat-labile enterotoxin (LT) of Escherichia coli, the latter when expressed in V. cholerae. Both toxins are also potent immunoadjuvants. Mutant LT molecules that retain immunoadjuvant properties while possessing markedly diminished enterotoxic activities when expressed by E. coli have been developed. One such mutant LT molecule has the substitution of a glycine residue for arginine-192 [LT((R192G))]. Live attenuated strains of V. cholerae that have been used both as V. cholerae vaccines and as vectors for inducing mucosal and systemic immune responses directed against expressed heterologous antigens have been developed. In order to ascertain whether LT((R192G)) can act as an immunoadjuvant when expressed in vivo by V. cholerae, we introduced a plasmid (pCS95) expressing this molecule into three vaccine strains of V. cholerae, Peru2, ETR3, and JRB14; the latter two strains contain genes encoding different heterologous antigens in the chromosome of the vaccine vectors. We found that LT((R192G)) was expressed from pCS95 in vitro by both E. coli and V. cholerae strains but that LT((R192G)) was detectable in the supernatant fraction of V. cholerae cultures only. In order to assess potential immunoadjuvanticity, groups of germfree mice were inoculated with the three V. cholerae vaccine strains alone and compared to groups inoculated with the V. cholerae vaccine strains supplemented with purified CT as an oral immunoadjuvant or V. cholerae vaccine strains expressing LT((R192G)) from pCS95. We found that mice continued to pass stool containing V. cholerae strains with pCS95 for at least 4 days after oral inoculation, the last day evaluated. We found that inoculation with V. cholerae vaccine strains containing pCS95 resulted in anti-LT((R192G)) immune responses, confirming in vivo expression. We were unable to detect immune responses directed against the heterologous antigens expressed at low levels in any group of animals, including animals that received purified CT as an immunoadjuvant. We were, however, able to measure increased vibriocidal immune responses against vaccine strains in animals that received V. cholerae vaccine strains expressing LT((R192G)) from pCS95 compared to the responses in animals that received V. cholerae vaccine strains alone. These results demonstrate that mutant LT molecules can be expressed in vivo by attenuated vaccine strains of V. cholerae and that such expression can result in an immunoadjuvant effect.